HUMANITARIZATION AS A FACTOR OF MODERNIZING EDUCATION IN A MODERN TECHNICAL UNIVERSITY - Ченбай, Н. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article highlights some aspects of the modernization of education in the contemporary technical university by strengthening its humanitarian component.